2016
DOI: 10.1097/md.0000000000005758
|View full text |Cite
|
Sign up to set email alerts
|

Adductor canal block versus femoral nerve block combined with sciatic nerve block as an anesthetic technique for hindfoot and ankle surgery

Abstract: Background:A femoral nerve block (FNB) in combination with a sciatic nerve block (SNB) is commonly used for anesthesia and analgesia in patients undergoing hindfoot and ankle surgery. The effects of FNB on motor function, related fall risk, and rehabilitation are controversial. An adductor canal block (ACB) potentially spares motor fibers in the femoral nerve, but the comparative effect on hindfoot and ankle surgeries between the 2 approaches is not yet well defined. We hypothesized that compared to FNB, ACB w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Only a few studies have mentioned PSS as a secondary outcome [33]. Fisker et al [34], Joe et al [35], and Hu et al [36] reported similar observations to those in the present study. There are few studies with postoperative follow-up in trauma patients [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…Only a few studies have mentioned PSS as a secondary outcome [33]. Fisker et al [34], Joe et al [35], and Hu et al [36] reported similar observations to those in the present study. There are few studies with postoperative follow-up in trauma patients [37][38][39].…”
Section: Discussionsupporting
confidence: 88%
“…The most important of these is FNB-related quadriceps weakness [ 2 , 16 , 17 ]. It has been suggested that blocking the femoral nerve more distally within the adductor canal could help prevent this effect [ 4 , 18 , 19 ]. However, adductor canal block is an advanced nerve block technique that is performed using US guidance.…”
Section: Discussionmentioning
confidence: 99%
“…Adductor Canal Block: The adductor canal block (ACB) which is more specifically referred as a saphenous nerve block in the adductor canal, is a single-shot or continuous technique for anesthesia and analgesia of the knee and medial leg 9 . The peripheral nerve block in adductor canal is very effective in the surgical operation procedures of knee and foot 10,11 . Van der Wal et al 12 was the first one who told about the adductor canal block using surface landmarks, while Manickam et al 13 used block at adductor canal for surgical operation procedures of knee under ultrasound guidance.…”
Section: Therapeutic Consideration Of Urvi Marmamentioning
confidence: 99%